2019
DOI: 10.3390/nu11122901
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Herbs and Spices on Increasing the Appreciation and Intake of Low-Salt Legume-Based Meals

Abstract: Flavoring using blends of herbs and spices (H&S) instead of salt may be a promising approach to increase legume consumption and reduce salt content in foods. This study examines the effects of H&S on the appreciation and intake of low-salt legume-based dishes in a real ecological eating environment. Four mezzes with standard (0.8% w/w) (S) or lower (0.4% w/w) (LS) salt level and with or without H&S (LSHS, SHS) were developed. In a randomized cross-over trial, 94 participants attended four sessions, one week ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…This highlights the need of the food industry to lower the content of salt in processed foods and in food service to make sure that the current high salt content found in the average diet is not "transferred" to a plant-based diet [61,62]. A recent study showed that the addition of herbs and spices is a feasible strategy for achieving a 50% reduction in salt content without compromising hedonic appreciation [63]. Excess dietary sodium has been found to have a major role in the pathogenesis of hypertension, a leading risk factor for premature death in the world, as it has an effect on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need of the food industry to lower the content of salt in processed foods and in food service to make sure that the current high salt content found in the average diet is not "transferred" to a plant-based diet [61,62]. A recent study showed that the addition of herbs and spices is a feasible strategy for achieving a 50% reduction in salt content without compromising hedonic appreciation [63]. Excess dietary sodium has been found to have a major role in the pathogenesis of hypertension, a leading risk factor for premature death in the world, as it has an effect on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Flavor and texture are characteristics that consumers consider when purchasing dry beans, influencing their decisions regarding market class and product type (Castellanos et al 1997;Scott and Maideni 1998;Leterme and Carmenza Muñoz 2002;Eihusen and Albrecht 2007;Winham et al 2019). However, for many consumers, beans are not palatable, and the beany flavor they impart when used as ingredients is often perceived as undesirable (Nachay 2017;Dougkas et al 2019). Therefore, improving dry bean flavor and texture through breeding has the potential to increase consumer acceptance and utilization of beans and inclusion of beans as ingredients in products while appealing to consumers' interest in flavor without many additives.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In plant‐based protein meals composed of legumes, the influence of various spice blends on consumer acceptance was investigated as the salt content was reduced. Mean overall liking and relative mean taste liking were higher for the treatments containing the cumin spice blend, compared to their same salt spice‐free blend counterpart (Dougkas et al., 2019).…”
Section: Resultsmentioning
confidence: 99%